New Reliability Index for Power System Protection Based On Multi-Agent Technique - Shalash, Nadheer A.; Abu Zaharin, Ahmad (2013)
A new index reliability for power system protection by optimizing the relay time operating using multi agent system (MAS) is presented. In the proposed method, the MAS consists of two agents as follows; first agent is a fault current agent, i.e., to determine the fault current at all points before and after grounding. While, the second agent is the time operating, i.e., to determine the time operating relay before and after modifying the fault current. The simulation implementation is carried out in Iraqi national grid system (132 kV) - Najaf city. The results show that the failure rate is decreased to 50% approximation for over current and earth fault relays.